Mental Health in Young Detainees Predicts Perpetration of and Desistance From Serious, Violent and Chronic Offending - Barra, Steffen; Turner, Daniel; Retz-Junginger, Petra; Hertz, Priscilla Gregorio; Rösler, Michael; Retz, Wolfgang (Frontiers in Psychiatry, 2022)
Mental health problems are common among young offenders but their role in predicting criminal recidivism is still not clear. Early identification and treatment of young offenders at risk of serious, violent, and chronic (SVC) offending is of major importance to increase their chances to develop into a healthy and non-criminal future and protect society from further crime. In the present study, we assessed mental health among 106 young offenders while incarcerated and analyzed their criminal careers up to 15 years after release. We found high rates of mental health issues, especially externalizing problems, but also concerning illegal substance and alcohol use patterns as well as personality disorders. Rule-breaking behavior and internalizing problems were negatively related to incarceration time until study assessment, but withdrawal and internalizing problems were positively associated with remaining time to release. Whereas SVC status before assessment and after release were not statistically dependent, mental health issues predicted perpetration of and desistance from SVC offending after release. Alarming alcohol use appeared to be of specific importance in this regard. Findings indicate that young offenders at risk of future SVC offending may benefit from mental health treatment with specific focus on problematic alcohol consumption to prevent ongoing crime perpetration.